Fundamentals of public relations and marketing communications in Canada - Lymer, Leah-Ann; Carney, William Wray, 1950- (Pica Pica Press, an imprint of The University of Alberta Press, 2015)
"Experts in public relations, marketing, and communications have created the most comprehensive textbook specifically for Canadian students and instructors. Logically organized to lead students from principles to their application--and generously supplemented with examples and case studies--the book features chapters on theory, history, law, ethics, research methods, planning, writing, marketing, advertising, media, and government relations, as well as digital, internal, and crisis communications. Chapters open with learning objectives and conclude with lists of key terms, review and discussion questions, activities, and recommended resources. Fundamentals of Public Relations and Marketing Communications in Canada will be essential in post-secondary classes and will serve as a valuable reference for established professionals and international communicators working in Canada."--